Assessing cost-effectiveness in the management of multiple sclerosis - Phillips, Ceri J (Dove Medical Press, 2009)
Multiple sclerosis (MS) is one of the most common causes of neurological disability in young and middle-aged adults, with current prevalence rates estimated to be 30 per 100,000 populations. Women are approximately twice as susceptible as males, but males are more likely to have progressive disease. The onset of the disease normally occurs between 20 and 40 years of age, with a peak incidence during the late twenties and early thirties, resulting in many years of disability for a large proportion of patients, many of whom require wheelchairs and some nursing home or hospital care. The aim of this study is to update a previous review which considered the cost-effectiveness of disease-modifying drugs (DMDs), such as interferons and glatiramer acetate, with more up to date therapies, such as mitaxantrone hydrochloride and natalizumab in the treatment of MS. The development and availability of new agents has been accompanied by an increased optimism that treatment regimens for MS would be more effective; that the number, severity and duration of relapses would diminish; that disease progression would be delayed; and that disability accumulation would be reduced. However, doubts have been expressed about the effectiveness of these treatments, which has only served to compound the problems associated with endeavors to estimate the relative cost-effectiveness of such interventions.